HIV-Infected Subjects With Poor CD4 T-Cell Recovery Despite Effective Therapy Express High Levels of OX40 and α4β7 on CD4 T-Cells Prior Therapy Initiation - Rosado-Sánchez, Isaac; Herrero-Fernández, Inés; Genebat, Miguel; Del Romero, Jorge; Riera, Melchor; Podzamczer, Daniel; Olalla, Julián; Vidal, Francesc; Muñoz-Fernández, Mª Angeles; Leal, Manuel; Pacheco, Yolanda M. (Frontiers in Immunology, 2018)
Background: HIV-infected subjects with suboptimal CD4 restoration despite suppressive cART (immunodiscordant subjects) have been classically characterized after a variable period of time under cART. Recently, we have reported that increased frequency of proliferating CD4 T-cells in these subjects is already present before the cART onset. The potential contribution of peripheral compensatory homeostatic proliferation (HP) is yet unknown. We aimed to analyze the expression of HP-related cellular markers on CD4 T-cells of immunodiscordant subjects before cART. Methods: We analyzed the expression of OX40 and α4β7 on peripheral CD4 T-cells from immunodiscordant and control subjects (n=21 each group) before cART initiation, and also on available follow-up samples (after 24 month of suppressive cART). Additionally, we tested the expression of these markers in an in vitro system for the study of human HP processes. Results: Immunodiscordant subjects showed increased levels of OX40 and α4β7 on CD4 T-cells before cART initiation. While the cART tended to reduce these levels, immunodiscordant subjects still maintained comparatively higher levels of OX40 and α4β7 after 24 months under suppressive cART. These HP-related markers were upregulated in vitro during the human HP, especially during the fast HP. Conclusions: Our results are compatible with exacerbated homeostatic proliferation processes in immunodiscordant subjects, already before the cART onset.